A Planning Checklist for Interprofessional Consultations for Women in Midwifery Care. (16th October 2018) - Phillippi, Julia C.; Holley, Sharon L.; Thompson, Jennifer L.; Virostko, Kate; Bennett, Kelly
Abstract: Team‐based, interprofessional models of maternity care can allow women to receive personalized care based on their health needs and personal preferences. However, involvement of multiple health care providers can fragment care and increase communication errors, which are a major cause of preventable maternal morbidity and mortality. In order to improve communication within one health system, a community‐engaged approach was used to develop a planning checklist for the care of women who began care with midwives but developed risks for poor perinatal outcomes. The planning checklist was constructed using feedback from women, nurses, midwives, and physicians in one interprofessional, collaborative network. In feasibility testing during 50 collaborative visits, the planning checklist provided a prompt to generate a comprehensive plan for maternity care and elucidate the rationale for interventions to women and future health care providers. In interviews after implementation of the checklist within a new collaborative format of prenatal physician consultations, women were pleased with the information received, and nurses, midwives, and physicians were positive about improved communication. This tool, developed with stakeholder input, was easy to implement and qualitatively beneficial to satisfaction and health system function. This article details the creation, implementation, and qualitative evaluation of the planning checklist. The checklist is provided and can be modified to meet the needs of other health systems.